2021
DOI: 10.3390/cancers13092123
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Global DNA Methylation Patterns in Human Melanoma Tissues and Their Derivative Cell Lines

Abstract: DNA methylation is a heritable epigenetic mark that is fundamental to mammalian development. Aberrant DNA methylation is an epigenetic hallmark of cancer cells. Cell lines are a critical in vitro model and very widely used to unravel mechanisms of cancer cell biology. However, limited data are available to assess whether DNA methylation patterns in tissues are retained when cell lines are established. Here, we provide the first genome-scale sequencing-based methylation map of metastatic melanoma tumour tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 77 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…Immortalized cell lines are widely used as an experimental model for the fundamental investigation of tumor cell biology. DNA methylation status has been demonstrated to be well conserved between tumor tissue samples and derivative cell lines; therefore, cell lines provide an effective in vitro model for studying epigenetic alterations in cancer cells [ 4 , 20 , 21 ]. Our editing system comprises three main components: a dCas9-SunTag targeting protein; locus-specific guide RNA (gRNA; sgRNA) construct; and an effector construct for manipulating DNA methylation ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immortalized cell lines are widely used as an experimental model for the fundamental investigation of tumor cell biology. DNA methylation status has been demonstrated to be well conserved between tumor tissue samples and derivative cell lines; therefore, cell lines provide an effective in vitro model for studying epigenetic alterations in cancer cells [ 4 , 20 , 21 ]. Our editing system comprises three main components: a dCas9-SunTag targeting protein; locus-specific guide RNA (gRNA; sgRNA) construct; and an effector construct for manipulating DNA methylation ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that overall breast cancer cell lines showed more aberrant DNAm (high DMI) than patient tumors (Supplementary Figure S4E,F). Higher DMI in cell lines in part maybe driven by culture condition induced epigenetic changes 86,87 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, melanoma tissue specimens, a diversity of patient treatment procedures could contribute to the heterogeneous molecular alterations observed in different studies. Moreover, adjacent tissue and lymphocyte infiltrates can influence the results of studies using tissue biopsies [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%